Chemical composition and biological activities of acetone extract from the seed peel of Madhuca elliptica - Truong, Duy H.; Nguyen, Ngoc An; Nguyen, Thi Linh; Dang, Thi Thuy Oanh; Ngo, Ngoc Hung; Huynh, Nguyen Tuong An; Nguyen, Quoc Hung; Vo, Van Thiep (Journal of Phytology, 2025)
This study explores the chemical composition and biological activities of the acetone extract derived from the seed peel of Madhuca elliptica (Sapotaceae family). Located in the Binh Chau - Phuoc Buu Nature Reserve of Vietnam, the seeds of M. elliptica were subjected to a methodical extraction process using acetone, followed by chemical analysis through Gas Chromatography-Mass Spectrometry (GC-MS). The analysis identified 35 distinct compounds, with a notable presence of cis-13 octadecenoic acid, n-hexadecanoic acid, octyl, diethyl phthalate, and octadecanoic acid. The biological efficacy of the extract was evaluated through two main bioassays: antioxidant and antibacterial activities. The antioxidant capacity was determined using the ABTS radical scavenging method, revealing a significant correlation between the concentration of the extract and its ability to neutralize free radicals, with an IC50 value of 6.259 ppm. Additionally, the antibacterial activity was assessed using the Kirby-Bauer disk diffusion method against a panel of both Gram-positive and Gram-negative bacteria. Through this research, M. elliptica exhibits significant potential due to its bioactive compounds, suggesting its applicability in pharmaceutical and nutraceutical fields. Besides, this study adds valuable insights into the utilizable aspects of M. elliptica, encouraging further research into its diverse applications.